Pattern of Pulmonary Function Test in Patients with Severe Mitral Stenosis (Bangladesh Critical Care Journal, 2015)
Background: The deterioration in lung function in mitral stenosis correlates with the severity of stenotic valves. A correlation is noted between vital capacity and the severity of dyspnoea in patients with mitral stenosis. This study tried to evaluate the pattern of pulmonary function test in patient with severe mitral stenosis.Materials & Methods: This study involving 56 patients of severe mitral stenosis was performed in a referral cardiovascular center at Dhaka, Bangladesh from January to September, 2011. Colour doppler echocardiography and pulmonary function test were performed in each cases. Forced vital capacity (FVC), forced expiratory volume in first second (FEV1), FEV1/FVC and peak expiratory flow (PEF) rate was assessed from pulmonary function test. Finally, pattern of pulmonary function test in severe mitral stenosis was assessed.Results: Amomg 56 patients, 46 were female with a male female ratio 1: 0.22 and the mean age of patients was 28.76 ± 7.2. Among patients with severe mitral stenosis, mean FEV1 (%) was 60.18 ± 13.054. Minimum FVC (%) was 26, maximum was 90 with mean 53.80 ± 12.313. The PEF varied from 150 to 330 L/minute with mean 223.75 ± 62.3251. In current study, out of 56 patients, 2 cases had obstructive type and rest of the patients had restricted type of airway on pulmonary function.Conclusion: The brief results of this study reveal that severe mitral stenosis is associated with impaired pulmonary function, usually presenting restrictive airway pattern.Bangladesh Crit Care J September 2014; 2 (2): 57-59